Donor-Acceptor Type Reduced Graphene-Oxide and a Tin-Selenide Nanohybrid With Broad and Ultrafast Optical Limiting Properties - Li, Xiaoqin; Wang, Yingwei; Wang, Yiduo; Wang, Hui; Qi, Xiang; He, Jun; Xiao, Si (Frontiers in Physics, 2020)
The nonlinear absorption properties of RGO have been studied extensively but the optical limiting (OL) performance of RGO was always confined to visible light. In this study, by anchoring SnSe nanosheets onto the surface of RGO, the SnSe/RGO nanohybrid shows a broader reverse saturable absorption (RSA), ranging from 400 nm to 800 nm, and enhanced nonlinear optical (NLO) response. The improvement of the NLO absorption response is attributed to a multiphoton-absorption process and electron-transfer effect in this artificially constructed donor-acceptor system. Pump-probe experiments suggest a response time of approximately 1.7-8 picoseconds for SnSe/RGO nanohybrid.